2016
DOI: 10.15628/holos.2016.4658
|View full text |Cite
|
Sign up to set email alerts
|

DISTURBANCES CAUSED BY FLOODS IN THREE PHYSICAL PROPERTIES OF A VERTISOL SOIL IN THE EAST REGION OF CUBA, CULTIVATED WITH SUGARCANE (Saccharum spp.)

Abstract: In Cuba the 40,3 % of cultivated lands is located in poorly drained soils, with tendency to increase, compounded by the effects of current climate change, which in this region of Cuba are becoming with more frequency in extreme climatic events such as droughts and floods. The research was developed with the objective of determining the influence of flooding in a Vertisol soil in three phisycal properties in the Cauto River Valley, of the Granma province, Cuba. It was considered the presence or absence of flood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Waterlogging reduces the stability of soil aggregates through colloid swelling [18]. In line with research [16] in a 10-day experiment, waterlogging on silty clay soils decreased by 2.2%. In this study, the measurement of water level (WL) uses an ultrasonic sensor HCRS04 as a distance sensor.…”
Section: Figure 7 Cumulative Daily Etosupporting
confidence: 80%
“…Waterlogging reduces the stability of soil aggregates through colloid swelling [18]. In line with research [16] in a 10-day experiment, waterlogging on silty clay soils decreased by 2.2%. In this study, the measurement of water level (WL) uses an ultrasonic sensor HCRS04 as a distance sensor.…”
Section: Figure 7 Cumulative Daily Etosupporting
confidence: 80%
“…Crop nutrient uptake and utilization are thus affected. Flooding promotes soil compaction which further destroys the soil structure through the breakdown of aggregates, deflocculation of clay, and destruction of cementing agents (Rodriguez et al, 2016). Flooding in coastal areas results in seawater intrusion into arable lands, creates high water tables and increases the salinity of soils (Mahmoodzadeh and Karamouz, 2017) which inhibits nitrogen uptake by crops.…”
Section: Crop Growth Challenges Under Flood and Drought Scenariosmentioning
confidence: 99%
“…Further studies have revealed that soil properties such as total porosity, moisture content, pH and organic carbon were higher after flooding than before, whereas others like bulk density, available P and total N were lower in the soil after flooding than before flooding (Rahman & Ranamukhaarachchi, 2003;Ubuoh, 2016;Njoku & Okoro, 2015). Flooding leads to both increases and decreases in soil nutrient content, with the former occurring by availing nutrients that are lacking in the soil (Ubuoh, 2016;Rodríguez et al, 2016). During flooding, floodwater dissolves and transports soil nutrients from flooding surfaces to adjacent rivers and vice versa through lateral flow (Ubuoh, 2016;Tsheboeng et al, 2014;Rahman & Ranamukhaarachchi, 2003).…”
Section: Introductionmentioning
confidence: 99%